Isolation and some properties of Be1 toxin from the venom of Brachistosternus ehrenbergii (Gervais, 1841) (Scorpiones:Bothriuridae) - Ramos, Catherina (2006)
By means of cationic exchange chromatography on CM-Sephadex C-25 column (16 x 1,1 cm) with ammonium acetate buffer 0,05 M at pH 7, from Brachistosternus ehrenbergii scorpion venom was isolated a protein with toxic activity on mice. In this system the toxin was ligated to gel and was eluated with buffer and NaCl 0,6M. The toxin denominated Be1 and it characterizes to be a basic protein that constitute 8,1% of venom total protein. Toxin purity was evaluated by electrophoresis in natives conditions, according to Reisfeld-method, and denaturants conditions by the Schägger-and-von Jagow-method, the toxin is a single chain polypeptide of 6,3 kDa has been determined. The inoculation of 60 μg toxin on albino mice, intraperitoneal way, produces some local signals as salival hipersecretion followed by respiratory affection, drags hind feet and finally 2 hours after, death. Intramuscular way (7,6 μg) Be1 produces temporal paralysis of the inoculated limb. The toxin has neither phospholipase, nor protease, nor acetylcholinesterase nor acetylcholinesterase inhibitor activity.